2013
DOI: 10.3109/0886022x.2013.815107
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-targeted peptides prevent on contrast-induced acute kidney injury in the rats with hypercholesterolemia

Abstract: Objective: The objective of this study is to evaluate the effect and mechanism of mitochondriatargeted peptides (MTP131 and SPI20) on contrast-induced acute kidney injury (CI-AKI) in rats with hypercholesterolemia. Method: Forty SD rats were randomly divided into normal diet group (NN, n ¼ 8) and high cholesterol supplemented dietary group (HN, n ¼ 32). At the end of 8 weeks, the group HN was divided into four subgroups. All Rats were given injection of either diatrizoate (10 mL/kg) or equal volume of normal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
(27 reference statements)
2
17
0
Order By: Relevance
“…In a recent report, both SS-31 and SS-20 significantly reduced oxidative stress and renal injury in rats given diatrizoate. 76 These studies highlight the number of drug-induced toxicities that appear to be mediated by mitochondrial impairment and suggest that SS-31 can significantly protect against such toxicities caused by diverse chemical compounds.…”
Section: Protection Against Herbicide-and Drug-induced Mitochondrial mentioning
confidence: 97%
“…In a recent report, both SS-31 and SS-20 significantly reduced oxidative stress and renal injury in rats given diatrizoate. 76 These studies highlight the number of drug-induced toxicities that appear to be mediated by mitochondrial impairment and suggest that SS-31 can significantly protect against such toxicities caused by diverse chemical compounds.…”
Section: Protection Against Herbicide-and Drug-induced Mitochondrial mentioning
confidence: 97%
“…This review will concentrate on the most recent findings and those preclinical studies that have provided the rationale for clinical trials with SS‐31. In addition to studies described in detail below, SS‐31 has been reported to be beneficial for chronic kidney disease, metabolic syndrome, neurodegenerative diseases and drug‐induced mitochondrial toxicity (Petri et al ., ; Mizuguchi et al ., ; Anderson et al ., ; Yang et al ., ; Duan et al ., ; Huang et al ., ; Toyama et al ., ). It should be pointed out that SS‐31 is also referred to as MTP‐131 or Bendavia in the literature.…”
Section: Therapeutic Potential Of Ss‐31 In Age‐associated Diseasesmentioning
confidence: 99%
“…SS-31 pretreatment also serves a protective role against hypoxia-/reoxygenation-induced apoptosis of human renal tubular epithelial cells, partly by suppression of p66Shc (Zhao et al 2013), a gene that encodes for an adaptor protein that regulates oxidative stress and apoptosis. Moreover, intraperitoneal injections of SS-31 in rats alleviate contrast-induced AKI, primarily due to an antioxidant action (Duan et al 2013). …”
Section: Renal Mitochondrial Targetingmentioning
confidence: 99%